Treatment situation in metastastic Castration Naive Prostate Cancer (mCRPC) and the implications on clinical routine Therapiesituation beim metastasierten kastrationsnaiven Prostatakarzinom (mCNPC) und die Auswirkungen im klinischen Alltag - Wülfing, C.; Bögemann, M.; Goebell, Peter; Hammerer, P.; Machtens, S.; Pfister, D.; Schwentner, C.; Steuber, T.; von Amsberg, G.; Schostak, M. (Urologe, 2019)
There is an ongoing change of paradigm in the treatment of metastatic prostate cancer (mPC). Taxan-based chemotherapy demonstrated a prolonged survival of patients in several randomized phase III trials. This is true in the situation of metastatic castration-resistent prostate cancer (mCRPC) as well as in the hormone-naïve stage (metastatic castration-naive PC [mCNPC]). In patients with mCNPC, treatment with docetaxel in combination with androgen deprivation therapy (ADT) prolonged the median total survival time by 15 months in comparison to ADT alone. Comparable results were obtained by the endocrine combination treatment with ADT/abiraterone. With the current data in mind it seems to be useful to discuss the value of early combination therapy with ADT/docetaxel or ADT/abiraterone as well as the impact on further treatment options in the mCRPC setting and to define criteria for treatment decisions in clinical practice.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Androgen deprivation therapy (ADT)/abiraterone; Androgen deprivation therapy (ADT)/docetaxel; Metastatic prostate cancer; Monitoring; Systemic therapy